Normative Review of Economic Democracy In The Indonesian Sharia Banking Legal Framework - Riza Hafizi, Muhammad; Rahman, Zainur (Jurnal Ilmu Hukum Tambun Bungai, 2024)
This research is a normative review of economic democracy within the legal framework of Indonesian sharia banking. In this context, this article aims to explore how the principles of economic democracy are reflected in the legal regulation of Islamic banking in Indonesia. The research method used is a normative approach involving a literature review and legal analysis of sharia banking regulations in Indonesia. The research results show that bank regulations in Law no. 7 of 1992, Law no. 10 and 21 of 1998, as well as other regulations, consistently promote democratic principles in Indonesia's national financial system. The Indonesian sharia banking institutional system which began in December 1983 marked an important first step in integrating sharia principles into the national banking system. Apart from that, the importance of the prudential principle in regulating sharia banking in Indonesia is also emphasized in this research. The precautionary principle aims to ensure that banks operate legally and in accordance with the principles of sharia law, as well as to protect consumer interests. This research provides valuable insight into how economic democracy is reflected in Indonesia's Islamic banking legal framework. The implications of these findings can be used to increase understanding of the importance of economic democracy in building an inclusive and sustainable financial system in Indonesia.